Analysis of The Economic Impact of Covid 19 on Performance Tourism Business Personnel in Belitung District - Valeriani, Devi; Wibawa, Dian Prihardini; Rendy, Rendy; Rianto, Rianto (Institut Pariwisata Trisakti, 2023)
This study aims to determine the influence of marketing, finance, production, human resources, creativity, and innovation on the performance of tourism business actors. This research is a quantitative descriptive study using simple random sampling. The population consisted of 18,591 business actors in the Belitung Regency, with a sample size of 100 using the Slovin formula. The partial results show that marketing and production have no significant effect on tourism business actor performance, while finance, human resources, creativity, and innovation have a significant impact. Due to constraints such as access, mobility, purchasing power, and societal fear, marketing does not affect tourism business performance. Finance affects the performance of tourism business actors by maintaining business liquidity, improving resilience, and providing access to financing for future expansion. Production activities do not affect tourism business performance as they focus more on service provision, optimizing marketing, financial management, and adjusting business models. Human resources significantly impact tourism business actor performance because skilled employees help maintain service quality, implement health and safety protocols, and adapt to changes. Creativity and innovation positively impact tourism business actor performance by creating new products, improving efficiency, and differentiating from competitors. Keywords: Marketing, Finance, Production, Human Resources, Creativity And Innovation, Tourism Business Actors Performance